CONCEPTIONS OF JUSTICE AND MEASURES OF EFFICIENCY: FORMATION OF THE PEOPLE’S POSITIONS ON PROGRESSIVE TAXES AND LEGAL ABORTION ISSUES IN LITHUANIAIN TERMS OF COGNITIVE SCHEMA THEORIES - Petronytė, Ieva (Politologija, 2015)
The correspondence between public policies and the will of citizens is acknowledged with not much of doubt as the ideal and the main principle of the representative democracy. However, the question remains how the attitudes of citizens are formed. One of the possible explanations is grounded on the idea of cognitive shortcuts and specifically on recently neglected idea of cognitive schemata: people are using cognitive schemas (or specific mental frameworks, structures of knowledge) in the situations where their opinion (even on certain previously unconsidered question) is needed. Schemas are used as the mechanisms which empower people to form opinion on policy issues. Findings from Western countries indicate political ideologies as the main cognitive schemas which help to form opinions in political field. In post-soviet countries such as Lithuania, however, such importance of ideology could be debated because of the low stability of party system, high volatility of citizens’ electoral preferences and prevailing overall absence of the consistent ideological sets of peoples’ attitudes. In this paper, first results of the empirical research on latent structures forming the opinions on policy issues in Lithuania are presented. The revised schema theory is used as the theoretical background for the analysis of citizens’ attitudes on two policy issues: introduction of progressive taxes and prohibition of abortion. By employing the method of semi-structured interviews eight cognitive schemas (four in each of the two fields) are found. In the sphere of the informants’ views on progressive taxes introduction, these schemas concentrates on the categories of social justice (attitude on the progressive tax issue is formed relying on concepts of solidarity, society’s responsibility and relative importance of the earnings’ size in the different income levels), “meritocratic” justice (attitude is formed through the logic of perceived injustice when harming with the progressive taxes people, who achieved more because of their successful efforts), equality-based justice (main principle held according to which the attitude is formed is simple equal hurts for all) and rational evaluation of policy efficiency (attitude is formed during some cost-benefit analysis of the proposed policy; the position on issue is positive if such concepts as mollification of public sphere prevails during the formation of attitude and negative if efficiency is measured through the capital outflow and citizens’ frauds while collecting taxes). The position on the abolition of abortion meanwhile is formed using such cognitive structures, which are either same rational evaluation of policy efficiency schema (position is grounded in cost-benefit analysis based on illegal and health endangering operations, social integration of abandoned children, shrinking population), or schemas, in their central categories corresponding to belief-structures such as catholic worldview (position is openly based on strict dogmas), humanism (in terms of emphasized value of human life itself, on which policy preference is based) or individualism (central are concepts of individual choice and right of decision). As it could be seen, two superschemas can be defined (ignoring the level of abstraction though) – one based on loosely called moral principles (different notions of justice and traditional value-loaded belief systems), and one based on rational evaluation of efficiency (both of these superstructures are found behind both issues: behind possibly more economic, efficient-related field of progressive taxes, and the traditionally more moral-related topic of abortion abolition). This empirical evidence could add to the more normative discussion on blurring lines between different principles marking specific political fields. Hence in this article the logic of arguments which leads to formation of specific positions on two policy issues in Lithuania is explored. Although this pilot research lacks representativeness and final list of cognitive schemas possible, it still not only registers main arguments on two issues, but also adds to deeper knowledge of the electorate, possible forecasts of political attitudes and, finally, may strengthen the ground for more meaningful communication between political elite and citizenry.